ARCHAEOLOGY OF MALA MIDDLE VALLEY IN LATE PERIOD, CAÑETE-LIMA - Taira Custodio, Johnny (2015)
This article is the result of surveys conducted in the middle valley of Mala, from the Annex to the Checas, Minay during the tour could identify four archaeological sites and two areas with petroglyphs have no archaeological or ethnohistorical reference. As I intend these findings contribute to better understanding and study of this part of the valley which has been long forgotten. These sites present an architecture and ceramics that can be dated as Late periods (Intermediate and Late Horizon).